A comparative prospective study of retrograde nailing versus locked compression plating in distal third femur fractures - Deepthi, Sabavath; Priyanka, Mise; Habeeb, Fatima Heba; S., Bharath Kumar (International Journal of Research in Orthopaedics, 2024)
Background: Treatment of distal femur fractures is complicated by the fact that the majority of these fractures occur near to transverse neurovascular structures. Present study aimed to assess the outcome in patients undergoing retrograde nailing vs locked compression plating in distal third femur fractures. Methods: The present prospective study was conducted among all the patients visiting Mamata general hospital Khammam with distal third femur fractures between age 18-80 years during the period of October 2020- September 2022. The patients were treated with retrograde nailing in group and locked compression plating in another group of patients with distal third femur fracture. Results: On assessment of the clinical outcome during the follow-up period, there is significantly lower clinical outcome score among the patients in the nailing group compared to the plate. Similarly, the radiological scores between the groups, there is significantly higher mean score among the patients in the nail group compared to the plate group. Conclusions: The present study showed a significant clinical outcome and radiological score among the patients treated with retrograde nailing compared to the patients treated with locking compression plating technique for distal third fracture of femur.